2015
DOI: 10.18535/jmscr/v3i10.37
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Cytological Findings In Patients with Superficial Lymphadenopathy: A Five Year Retrospective Study

Abstract: Superficial lymphadenopathy is ranked among the most common clinical findings encountered in medical practice. Fine needle aspiration cytology (FNAC) is a veritable tool for the assessment and diagnosis of superficial lymph node enlargement. The aim of our study is to see the profile of superficial lymphadenopathy in our region and the role of FNAC in the definite diagnosis of cause of lymphadenopathy. In this 5 years study a total of 1188 patients with superficial lymphadenopathy were referred from the out pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
0
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
6
0
0
Order By: Relevance
“…It may be due to various reasons, ranges from reactive, inflammatory to malignancies. Sometime, the patient present withlymphnode enlargement as initi search for the primary.Our results are comparable with other Indian study with males more affected than females (1.2:1) and where majority of the cases belonged to age group of 1 reactive lymphadenitis (52.3%) [7]. We also observed in our study that majority of the patients belonging to pediatric age group, under 14 years, presented with reactive lymphadenitis in 171 cases (11.1%) of granulomatous lymphadenitis.These results are comparable with other Indian studies, where, in older age, more than 65 years of age, the major cause of lymphadenopathy is metastatic deposits [8].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It may be due to various reasons, ranges from reactive, inflammatory to malignancies. Sometime, the patient present withlymphnode enlargement as initi search for the primary.Our results are comparable with other Indian study with males more affected than females (1.2:1) and where majority of the cases belonged to age group of 1 reactive lymphadenitis (52.3%) [7]. We also observed in our study that majority of the patients belonging to pediatric age group, under 14 years, presented with reactive lymphadenitis in 171 cases (11.1%) of granulomatous lymphadenitis.These results are comparable with other Indian studies, where, in older age, more than 65 years of age, the major cause of lymphadenopathy is metastatic deposits [8].…”
Section: Discussionsupporting
confidence: 90%
“…In our present study, we observed that most common site of lymph node enlargement was cervical group of lymph nodes, followed by axillary group of lymph nodes and inguinal group of lymph nodes. Similar observations were also reported by other Indian studies [3,7,9]. In all these group of lym lymphadenitis followed by granulomatous lymphadenitis which is similar to studies done by Pandey P et al [4].…”
Section: Malignant Melanoma Total (71) 55 4supporting
confidence: 91%
See 3 more Smart Citations